A new perspective on concepts of asthma severity and control - Taylor, D R; Bateman, E D; Boulet, L-P; Boushey, H A; Busse, W W; Casale, T B; Chanez, P; Enright, P L; Gibson, P G; de Jongste, J C; Kerstjens, H A M; Lazarus, S C; et al. (The European respiratory journal, 2008)
Concepts of asthma severity and control are important in the evaluation of patients and their response to treatment but the terminology is not standardised and the terms are often used interchangeably. This review, arising from the work of an American Thoracic Society/European Respiratory Society Task Force, identifies the need for separate concepts of control and severity, describes their evolution in asthma guidelines and provides a framework for understanding the relationship between current concepts of asthma phenotype, severity and control. "Asthma control" refers to the extent to which the manifestations of asthma have been reduced or removed by treatment. Its assessment should incorporate the dual components of current clinical control (e.g. symptoms, reliever use and lung function) and future risk (e.g. exacerbations and lung function decline). The most clinically useful concept of asthma severity is based on the intensity of treatment required to achieve good asthma control, i.e. severity is assessed during treatment. Severe asthma is defined as the requirement for (not necessarily just prescription or use of) high-intensity treatment. Asthma severity may be influenced by the underlying disease activity and by the patient's phenotype, both of which may be further described using pathological and physiological markers. These markers can also act as surrogate measures for future risk.